CONDITIONS FOR THE FORMATION OF PROFESSIONAL COMPETENCIES OF THE OFFICER CORPS OF THE NATIONAL GUARD OF UKRAINE AS ONE OF THE COMPONENTS OF READINESS TO PERFORM TASKS AS DESIGNATED - Panchenko, Vitalii; Sydorenko, Iryna; Yakobchuk, Mykhailo (Honor and Law, 2025)
The conditions for the formation of professional competencies of the officers of the National Guard of Ukraine as one of the important factors in ensuring readiness to perform official (combat) tasks as assigned are analysed. The key professional competencies of an officer in the context of military personnel activities are identified, and the basic components and factors influencing the formation of these competencies are highlighted.